Penyuluhan Kewirausahaan Untuk Pemula : Sekolah Binaan Desa Lembah Alas - Fitra Jaya; Try Rasid Desky; Iswandi Walad; Khairuddin Nasution; Geri Suherman (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
Entrepreneurs are people with a creative and innovative spirit who are able to build, construct, develop, advance and make their company superior. The term entrepreneur has the same meaning as merchant, but the meaning is different. This counseling is aimed at students at the Lembah Village assisted school because the education it teaches focuses on skills or vocations whose graduates do not go to college but do not work and are independent businesses. Participants are given the opportunity to ask questions after receiving an explanation from the speaker, so that participants can receive complete information. Participants can also ask questions about things they don't know or have problems with when they are doing business. This Community Service Activity will be held on the day/date: Thursday, December 11 2024. . time 08.00 to 13.00 WIB